2018
DOI: 10.3390/asi1030032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Roughness on Early Stage Oxidation Behavior of Ni-Base Superalloy IN 625

Abstract: Abstract:In the present work the effect of surface roughness on oxidation behavior during the early stages of high temperature exposure of Ni-base superalloy IN 625 is described. The surface roughness was described using standard contact profilometer as well as novel method, fractal analysis. It was found that the different surface preparation resulted in a difference in roughness with a parameter increase of at least one order of magnitude for the ground sample as compared with the polished sample. The oxidat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…For materials used at elevated temperatures, their oxidation resistance and equally their lifetime at high temperatures become to be a crucial factor during materials engineering. It was found that different surface preparations result in a different oxidation behavior of a wide range of alloys, e.g., Ni-base superalloys [10][11][12][13][14][15], iron [16], or Fe-base alloys [17][18][19][20][21]. Surface preparation significantly influences the oxidation behavior of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…For materials used at elevated temperatures, their oxidation resistance and equally their lifetime at high temperatures become to be a crucial factor during materials engineering. It was found that different surface preparations result in a different oxidation behavior of a wide range of alloys, e.g., Ni-base superalloys [10][11][12][13][14][15], iron [16], or Fe-base alloys [17][18][19][20][21]. Surface preparation significantly influences the oxidation behavior of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…It is of interest that the relative amount of oxygen depends on the surface roughness rather than the research atmosphere (air or Ar). This can be explained by the fact that the geometric area of a rough surface is larger than that of a smooth surface and therefore an oxidation results in a larger scale [23]. Also, relatively high oxygen content on the surface may be caused by oxygen contamination from air.…”
Section: Resultsmentioning
confidence: 99%
“…The samples synthesized at a higher temperature and a shorter time appear to increase start-up oxidation temperatures. However, surface roughness was shown to play a role in the oxidation behavior of several materials [51][52][53][54][55][56]. Platt et al [54] reported that there is a clear trend towards rougher surfaces generating thicker oxides.…”
Section: Siliconizing Stepmentioning
confidence: 99%